2021
DOI: 10.1097/j.pain.0000000000002434
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned pain modulation is more efficient in patients with painful diabetic polyneuropathy than those with nonpainful diabetic polyneuropathy

Abstract: Unlike other chronic pain syndromes, conditioned pain modulation is more efficient in painful than non-painful diabetic neuropathy patients, possibly due to the peripheral neuropathic sensory changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 56 publications
3
12
0
Order By: Relevance
“…Taken together these findings support our finding that the strongest correlation of heat-based CPM with a clinical pain measure was with the painDETECT scores (an assessment of neuropathic pain). A link between neuropathic pain and CPM particularly in heat-based paradigm but not a pressure paradigm, was also recently found in a study of CPM effects using heat and pressure test paradigms in people with painful and non-painful diabetic polyneuropathy (DPN) ( 30 ). This study reported that the inhibitory CPM evoked by heat was significantly correlated with greater neuropathic pain ( 30 ).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Taken together these findings support our finding that the strongest correlation of heat-based CPM with a clinical pain measure was with the painDETECT scores (an assessment of neuropathic pain). A link between neuropathic pain and CPM particularly in heat-based paradigm but not a pressure paradigm, was also recently found in a study of CPM effects using heat and pressure test paradigms in people with painful and non-painful diabetic polyneuropathy (DPN) ( 30 ). This study reported that the inhibitory CPM evoked by heat was significantly correlated with greater neuropathic pain ( 30 ).…”
Section: Discussionmentioning
confidence: 65%
“…A link between neuropathic pain and CPM particularly in heat-based paradigm but not a pressure paradigm, was also recently found in a study of CPM effects using heat and pressure test paradigms in people with painful and non-painful diabetic polyneuropathy (DPN) ( 30 ). This study reported that the inhibitory CPM evoked by heat was significantly correlated with greater neuropathic pain ( 30 ). This suggests that in our population of people with chronic pain, the severity of their clinical pain and its interference on activities of daily living may not greatly impact their ability to exhibit an experimentally-induced CPM.…”
Section: Discussionmentioning
confidence: 65%
“… 14 The same author found more efficient CPM among patients with painful diabetic neuropathy in comparison with those patients with painless diabetic neuropathy, which might result from altered sensory messages coming from tested affected body sites. 15 Cold inhibition has been found greatest during the menstrual phases when comparing the ovulatory phase to the menstrual and luteal phases. 47 It is difficult to draw any conclusion concerning the role of hormones in CPM because another study could not determine any variation of CPM during the menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The conditioning stimulus in the conditioned pain modulation paradigm is often applied to the upper or lower limbs, which may confound pain‐inhibitory effects in people with enhanced or diminished sensation in the limbs due to peripheral neuropathy (Granovsky et al, 2021). The present findings suggest that temple cooling inhibits pressure pain on the hand afterwards, and thus might be an appropriate conditioning stimulus in future research examining pain inhibition in people with peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%